Outside money: The advantages of owning the magic porridge pot - L. Randall Wray (Levy Economics Institute of Bard College, 2014)
Over the past two decades there has been a revival of Georg Friedrich Knapp's "state money" approach, also known as chartalism. The modern version has come to be called Modern Money Theory. Much of the recent research has delved into three main areas: mining previous work, applying the theory to analysis of current sovereign monetary operations, and exploring the policy space open to sovereign currency issuers. This paper focuses on "outside" money - the currency issued by the sovereign - and the advantages that accrue to nations that make full use of the policy space provided by outside money.
Keywords: B1; B2; B3; B5; E5; E6; 330; Central Bank Independence; Chartalism; Fiat Money; Functional Finance; Innes; Keynes; Knapp; Modern Money Theory; Outside Money; Sovereign Currency; State Money